Geometria de Weyl e A teoria gravitacional de Nordström - Almeida, Tony Silva (2010)
In this disssertation we are concerned with Nordström s scalar gravity theory, one of the first attempts to formulate a relativistic theory of gravitation. We start be describing the theory in its original formulation given by Nordström. We then proceed to show how Nordström s approach is equivalent to a metric theory of gravity which regards gravity as a manifestation of spacetime curvature, a result first obtained by Einstein and Fokker in 1914. We exlore this formal equivalence between the two approaches to derive Nordström s predictions of some observed phenomena, such as Mercury s perihelium and the time delay of the light. finally we consider a third approach which makes use of Weyl geometry through its concept of gauge transformations. We then show that one can regard both Nordström s and Einstein-Fokker s framework as equivalent to a theory formulated to a theory formulated in minkowski spacetime in which the gravitational field is encoded in a non-trivial affine connection.